Architectures of life and death the eco-aesthetics of the built environment - Radman, Andrej, 1968-; Kousoulas, Stavros (Rowman & Littlefield, 2021)
"Interdisciplinary in approach, this book combines philosophy, hybrid theory, and architectural theory with case studies, explicitly linking the traditions together to investigate the eco-aesthetics of the urban environment"--